Contemporary Trends in Pulsed Field Ablation for Cardiac Arrhythmias - Hagai Yavin; Mark Prasad; Jonathan Gordon; Tolga Aksu; Henry D. Huang (Journal of Cardiovascular Development and Disease)
Pulsed field ablation (PFA) is a catheter-based procedure that utilizes short high voltage and short-duration electrical field pulses to induce tissue injury. The last decade has yielded significant scientific progress and quickened interest in PFA as an energy modality leading to the emergence of the clinical use of PFA technologies for the treatment of atrial fibrillation. It is generally agreed that more research is needed to improve our biophysical understanding of PFA for clinical cardiac applications as well as its potential as a potential alternative energy source to thermal ablation modalities for the treatment of other arrhythmias. In this review, we discuss the available preclinical and clinical evidence for PFA for atrial fibrillation, developments for ventricular arrhythmia (VA) ablation, and future perspectives.